Proof of guilt : Barbara Graham and the politics of executing women in America - Cairns, Kathleen A., 1946- (University of Nebraska Press, 2013)
"Proof of Guilt is a fascinating book that details the case of Barbara Graham and also explores the issue of the execution of women. Although the Graham case occurred decades ago, Cairns brings Barbara Graham back to life in this compelling narrative. The book sheds new light on the issue of the death penalty and dispels many myths and misconceptions surrounding it."-Gloria Killian, exonerée and coauthor of Full Circle: A True Story of Murder, Lies, and Vindication